Classi fication of motor imagery tasks based on BCI paradigm - Hossain, Nahid; Hasan, Bhuiyan Itmam; Mohona, Mahfuza Humayra; Noshin, Kantat Rehnuma (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.